Military Background, Political Connection, Audit Quality And Earning Quality - Arif Widodo; Zaenal Fanani (Jurnal Akuntansi, 2020)
This research is try to determine the effect of military background and political connections on earning quality with audit quality as a mediator. This research uses a quantitative approach using a sample of mining sector company that listing in Indonesia Stock Exchange in the 2017-2018 periods. The conclusion of this research points out that military background has positive effect on audit quality and political connections negatively affect earning quality. While earning quality not effected by the military background, political connections do not effect audit quality, and earnings quality not effected by audit quality. Likewise, for the hypothesis, mediation of the audit quality has no effect on the relationship of military background and political connections to earnings quality.